2010
DOI: 10.1007/s00384-010-1086-3
|View full text |Cite
|
Sign up to set email alerts
|

Renal impairment caused by temporary loop ileostomy

Abstract: Renal impairment is a well-known potential complication of loop ileostomy. To avoid this complication, close control and backup support is recommended in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 23 publications
2
51
0
2
Order By: Relevance
“…Our findings of risk for dehydration and need for readmission and impact on renal function are consistent with prior reports from diverse reporting centers demonstrating that the challenges are universal and still need further study. [1,2] Perhaps the greatest opportunity for improvement is through interventions to manage the volume of ileostomy output. There are existing guidelines and algorithms regarding treatment of high output stomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings of risk for dehydration and need for readmission and impact on renal function are consistent with prior reports from diverse reporting centers demonstrating that the challenges are universal and still need further study. [1,2] Perhaps the greatest opportunity for improvement is through interventions to manage the volume of ileostomy output. There are existing guidelines and algorithms regarding treatment of high output stomas.…”
Section: Discussionmentioning
confidence: 99%
“…[1] In addition, a prospective cohort study demonstrated that all patients with diverting ileostomies had a significant decrease in their glomerular filtration rates measured just prior to ileostomy closure compared to just after ileostomy creation. [2] Other ileostomy-related complications such as small bowel obstruction, stoma necrosis, prolapse, or retraction may not only result in readmissions but may also require reoperation. Other less clinically serious complications such as leakage from the stoma appliance and skin irritation may lead to a decrease in the patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a stoma has been shown to consistently impair renal function, with clinical renal failure occurring in 20% of ileostomates 12 . Although readmissions are often multifactorial, dehydration represents a prevalent and potentially preventable target.…”
Section: Introductionmentioning
confidence: 99%
“…Dehydration is responsible for renal failure in 50% of cases who develop renal failure, and high stomal output is the dehydration culprit in 44% of cases. 6 These ratios are highly significant in patients undergoing LT and receiving immunosuppressant agents, as renal function is either already impaired or on the verge of impairment in a sizable number of patients undergoing LT. Additionally, calcineurin inhibitors, including cyclosporine and tacrolimus, and prophylactic antibiotics used after transplant are toxic to the kidneys. Therefore, hydration is significant, even in uncomplicated transplant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the liver is highly susceptible to iatrogenic injury during transplant, circulatory dysfunction may occur upon portal clamping, and damage to the gastrointestinal mucosal barrier can be induced by high-dose steroids, posttransplant complications are observed most commonly in gastrointestinal organs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Gastrointestinal complications are common among patients who undergo solid-organ transplant and range from mild to moderate conditions, such as diarrhea or nausea, to more severe, life-threatening complications such as digestive bleeding and gut perforation. 5 Gastrointestinal perforation (GIP), which is potentially lethal, may occur at any point in the gastrointestinal tract, including the stomach, jejunum, ileum, and colon.…”
Section: Introductionmentioning
confidence: 99%